A Critical Review of Recent Literature on Populism - Abromeit, John (2017)
This is a review article of the following five recent studies on populism: 1) Ruth Wodak’s The Politics of Fear: What Right-Wing Populist Discourses Mean (Sage, 2015); 2) Benjamin Moffitt’s The Global Rise of Populism: Performance, Political Style and Representation (Stanford University Press, 2016); 3) Cas Mudde and Cristóbal Rovira Kaltwasser’s Populism: A Very Short Introduction (Oxford University Press, 2017); 4) Jan-Werner Müller’s What is Populism? (University of Pennsylvania Press, 2016); and 5) John B. Judis’ The Populist Explosion: How the Great Recession Transformed American and European Politics (Columbia Global Reports, 2016). The review argues for a return to early Frankfurt School Critical Theory to address some of the shortcomings of these studies.